PENERAPAN PEER TUTORING UNTUK MENINGKATKAN PEMAHAMAN KONSEP JUMLAH DAN SELISIH SUDUT [THE IMPLEMENTATION OF PEER TUTORING TO IMPROVE CONCEPTUAL UNDERSTANDING OF SUM AND DIFFERENCE ANGLES] - Jacob S Seleky; Romualdus Ripa; Atalya Agustin (Polyglot, 2021)
Conceptual understanding is a student's ability to understand a concept that has been studied. Based on observation of daily test results, it is known that some students do not understand the concept of the sum and difference angle trigonometry formulas. This is demonstrated by achieving the standard of success of the number of students who achieved the Minimum Standard of Achievement set by the school of 75.  To improve the situation, researchers implemented the Peer Tutoring method, which aims to improve the understanding of the concept of the sum and difference angle trigonometry formulas and find out how the application of Peer Tutoring can improve the conceptual understanding of the student. This research uses the Class Action Research (CAR) method based on Kemmis & McTaggart spiral model. This research was conducted in grade XI MIPA 2 SMA YZ in Semarang with 23 students. Instruments used for data collection are daily tests, observation sheets, checklists of mentor teachers and other teachers, mentor teacher interviews, and research reflection journals. The data obtained is calculated using descriptive statistics and analyzed qualitatively descriptively. Based on the analysis results, it can be concluded that the implementation of Peer Tutoring could improve student's conceptual understanding of the sum and difference.  The increase was seen from the number of students who achieved the Minimum Standard of Achievement in the first cycle, which was 60.87% and in the second cycle was 78.26%. Therefore, the achievement has exceeded the standard of success is used, which was 75% of the number of students who reach the Minimum Standard of Achievement.BAHASA INDONESIA ABSTRACT: Pemahaman konsep adalah kemampuan siswa untuk memahami suatu konsep yang telah dipelajari. Berdasarkan observasi hasil tes harian, diketahui bahwa sebagian siswa belum memahami konsep rumus jumlah dan selisih sudut trigonometri. Hal tersebut ditunjukkan dengan belum tercapainya standar keberhasilan jumlah siswa yang mencapai Kriteria Ketuntasan Minimum (KKM) yang ditetapkan sekolah sebesar 75. Untuk memperbaiki keadaan tersebut, peneliti menerapkan metode Peer Tutoring, yang bertujuan selain untuk memperbaiki dan meningkatkan pemahaman konsep rumus jumlah dan selisih sudut trigonometri, juga untuk mengetahui bagaimana penerapan Peer Tutoring dapat meningkatkan pemahaman konsep siswa. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) berdasarkan model spiral Kemmis & McTaggart. Penelitian ini dilakukan pada kelas XI MIPA 2 SMA YZ di Semarang dengan jumlah siswa sebanyak 23 orang. Instrumen yang digunakan untuk pengumpulan data adalah tes harian, lembar observasi guru mentor dan guru lain, wawancara guru mentor, dan jurnal refleksi peneliti. Data yang diperoleh dikalkulasi menggunakan statistik deskriptif dan dianalisis secara kualitatif deskriptif. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan Peer Tutoring dapat meningkatkan pemahaman konsep rumus jumlah dan selisih sudut trigonometri pada siswa kelas XI MIPA 2 SMA YZ di Semarang. Peningkatan tersebut terlihat dari jumlah siswa yang mencapai Kriteria Ketuntasan Minimum (KKM) pada siklus pertama mencapai 60,87%, meningkat pada siklus kedua menjadi 78,26%. Pencapain tersebut telah melebihi standar keberhasilan yang digunakan yaitu 75% dari jumlah siswa yang mencapai KKM.